(untitled) (The Pretoria Student Law Review, 2021)
It is unquestioned that social media is present in almost every aspect of our daily lives. Due to the widespread accessibility of posts on social media, comments posted by a person in his/her personal capacity often boils over and negatively affects his/her role as an employee. Posts have the potential to either damage the reputation of an organisation directly or indirectly (the latter being caused by an employee’s mere association with the business). Defamatory posts are becoming more and more common and, consequently, social media misconduct clashes are finding their way into dispute resolutions forums. These disputes create a constant battle between the rights of an employer and the rights of an employee. Given that social media misconduct can be rather complex, it is imperative that employers are aware of the legislation governing misconduct to ensure that they are well-prepared to take preventative or swift action should the need arise.